PENGARUH SELF ESTEEM DAN SELF EFFICACY TERHADAP KINERJA PEGAWAI PERUM BULOG KANWIL LAMPUNG - Tri Lestira Putri Warganegara; Anindita Kartini (Jurnal Ekonomi dan Bisnis (EK dan BI), 2023)
The success of an organization is shaped by the performance of its employees. Every company will try to improve employee performance in order to achieve organizational goals that have been set.The purpose of this research is to determine the effect of self-esteem and self-efficacy on Perum Bulog, Regional Office of Lampung. This study uses a quantitative approach. The population sampling technique consists of 48 respondents. Using a questionnaire with a Likert scale. The research results obtained by testing the t test hypothesis on the Self-Esteem variable at a significant level of 5% or α = 0.05 as much as 0.000 <0.05 and t count (4.089) > t table (2.014), so Ha is accepted and Ho is rejected . The Self-Efficacy variable at a significant level of 5% or α = 0.05 is 0.000 <0.05 and t count (3.873) > t table (2.014), so Ha is accepted and Ho is rejected. Hypothesis test F with calculated F value (82.763) > F table (3.20) and sigma value < opportunity value 0.05 or 0.000 value < 0.05 so Ha is accepted and Ho is rejected which means self-esteem and self-efficacy simultaneously give a significant influence on Employee Performance.